2015
DOI: 10.1038/ncomms8297
|View full text |Cite
|
Sign up to set email alerts
|

Superconfinement tailors fluid flow at microscales

Abstract: Understanding fluid dynamics under extreme confinement, where device and intrinsic fluid length scales become comparable, is essential to successfully develop the coming generations of fluidic devices. Here we report measurements of advancing fluid fronts in such a regime, which we dub superconfinement. We find that the strong coupling between contact-line friction and geometric confinement gives rise to a new stability regime where the maximum speed for a stable moving front exhibits a distinctive response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Finally, experimental systems consisting of colloid-polymer mixtures are known to phase separate into colloid-rich and colloid-poor domains, with an interface width that is of order 1 µm (Aarts et al 2004;Setu et al 2015), much larger than the typical value for molecular fluids. Such a system can potentially be exploited to realise the different contact line slip regimes discussed here experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, experimental systems consisting of colloid-polymer mixtures are known to phase separate into colloid-rich and colloid-poor domains, with an interface width that is of order 1 µm (Aarts et al 2004;Setu et al 2015), much larger than the typical value for molecular fluids. Such a system can potentially be exploited to realise the different contact line slip regimes discussed here experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…When the liquid is only partially wetting, however, a critical plate velocity is needed for the liquid to coat the substrate [9,[27][28][29]. In the re-130 verse process of forced wetting transition in advancing contact lines, air is entrained, but at much higher contact line velocities [30][31][32][33][34][35][36][37]. Below the wetting transition, the contact line moves with the same velocity as the interface tip.…”
mentioning
confidence: 99%
“…Most existing microfluidic bubble generators rely on flow channels with ge-225 ometric constrictions [49][50][51][52] or an external cross-flow [53][54][55][56] to initiate bubble pinch-off [57][58][59]. Recently, it has been shown that "superconfinement" can trigger a jet instability from a moving interface in the absence of geometric features, but through a mechanism that relies on thermal fluctuations 230 in systems with ultralow surface tension [36]. Our experiments demonstrate that pinch-off will occur in smooth, uniform capillaries as a result of wettability-mediated contact line motion.…”
mentioning
confidence: 99%
“…This gives the advantage to easily incorporate complex physical phenomena in the algorithm, ranging from phase behavior, multiphase flows to chemical interactions between the fluid and the surrounding solid surfaces. Moreover, it avoids the need to track the time evolution of the interface between different phases [45], which makes it ideal to study problems involving the time evolution of fluid-fluid 100 interfaces [46,47].…”
mentioning
confidence: 99%